2021
DOI: 10.5114/pjr.2021.111360
|View full text |Cite
|
Sign up to set email alerts
|

Does diffusion-weighted magnetic resonance imaging help in the detection of renal parenchymal disease and staging/prognostication in chronic kidney disease?

Abstract: Purpose Diffusion-weighted imaging (DWI) in renal diseases is an upcoming modality, and its utility as an additional marker is yet to be proven. This study was intended to find the relationship between apparent diffusion coefficient (ADC) values with renal function tests and stages of chronic kidney disease (CKD) to assess renal dysfunction, and to label a cut-off for normal renal function and dysfunction. Material and methods A prospective diagnostic study was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Moreover, Emre et al revealed significant differences between all stage groups in terms of mean ADC values. In a recent study by Arora et al [18] that compared 60 patients with CKD to 60 healthy individuals without a history of CKD and high creatinine levels, the mean ADC values significantly differed in the CKD group at different stages. In addition, they found that the mean ADC values in the CKD group were significantly lower than those in the healthy control group.…”
Section: Emre Et Al Compared Creatinine Clearance and Renalmentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, Emre et al revealed significant differences between all stage groups in terms of mean ADC values. In a recent study by Arora et al [18] that compared 60 patients with CKD to 60 healthy individuals without a history of CKD and high creatinine levels, the mean ADC values significantly differed in the CKD group at different stages. In addition, they found that the mean ADC values in the CKD group were significantly lower than those in the healthy control group.…”
Section: Emre Et Al Compared Creatinine Clearance and Renalmentioning
confidence: 95%
“…We found that individuals with normal renal function can be differentiated from patients with dysfunction with 69.7% sensitivity and 87.7% specificity for measurements above the cut-off value of 1.944 (× 10 − 3mm 2 /s). Notably, Arora et al [18] found the cutoff value of 2.000 (× 10 − 3mm 2 /s) as an indicator of renal dysfunction. They reported that with the currently used cut-off value, the sensitivity is 56% and the specificity is 91%.…”
Section: F8and(@0a8:-! 8$eu#ttand:494:;! M4);=e=9=ev! M%4w=t=w=ev! Xx...mentioning
confidence: 99%